Workload in a group of Latin American teachers during the COVID-19 pandemic - Medina-Guillen, Leonardo Flavio (2021)
Introduction. The viral disease Covid-19 -currently a pandemic- forced to accommodate measures of social distancing with the intention of limiting its expansion, including: teleworking and online (virtual) teaching.  Would the sudden shift from face-to-face classroom to virtual education result in teacher work overload?  If so, what are the influencing factors? Objective. Analyze the workload of teachers in Latin America, at three different educational levels, during the COVID-19 pandemic in June and July 2020. Methods. Quantitative, descriptive, cross-sectional study. A 37-question questionnaire was used, with a Hernández-Nieto content validity coefficient of 0.99 and a temporal stability coefficient 0.91. Statistical analysis was performed using Excel 2019, measures of central tendency and frequency analysis were used.  Results. 887 teachers were surveyed for whom sociodemographic characteristics are detailed and their personal, technical, institutional and space load factors assessed.  Student dropout percentage was also ascertained.  Conclusion. The surveyed teachers perceived an increase in workload due to the factors studied, intertwined with an increase in student desertion.  The abrupt change in the modality from face-to-face to virtual education has generated a reorganization of work and family life, teleworking from home requires a clear delimitation by teachers of the work schedules and functions involved in the various aspects of online education.